Rectal Chlamydia trachomatis Infection: A Narrative Review of the State of the Science and Research Priorities. Issue 12 (December 2021) - Khosropour, Christine M.; Dombrowski, Julia C.; Vojtech, Lucia; Patton, Dorothy L.; Campbell, Lee Ann; Barbee, Lindley A.; Franzi, Michaela C.; Hybiske, Kevin
Abstract : Abstract: Chlamydia trachomatis (CT) is the most commonly reported infection in the United States. Most chlamydial research to date has focused on urogenital infection, but a growing body of research has demonstrated that rectal chlamydia is a relatively common infection among clinic-attending men and women. We know that most rectal CT infections are asymptomatic, but the health implications of these infections, particularly for women, are unclear. In addition, there are key knowledge gaps related to the epidemiologic parameters of rectal chlamydia, the routes of acquisition, the duration of infection, and the clinical significance of a positive rectal CT test result. This lack of information has led to a blind spot in the potential role of rectal chlamydia in sustaining high levels of CT transmission in the United States. Furthermore, recent findings from animal models suggest that the immune response generated from gastrointestinal chlamydial infection can protect against urogenital infection; however, it remains to be determined whether rectal chlamydia similarly modulates anti-CT immunity in humans. This is a critical question in the context of ongoing efforts to develop a CT vaccine. In this narrative review, we summarize the state of the science for rectal chlamydia and discuss the key outstanding questions and research priorities in this neglected area of sexual health research. Abstract : Rectal Chlamydia trachomatis is a commonly diagnosed infection, but there are key gaps in our understanding of the clinical, epidemiologic, and biologic aspects of infection.Supplemental digital content is available in the text.